Hypothyroidism: A Rare Cause of the Bilateral Carpal Tunnel Syndrome—A Case Report and a Review of the Literature - Chisholm, Joseph C. (1981)
Reported herein is a patient who developed symptoms of bilateral carpal tunnel syndrome following radioactive iodine induced hypothyroidism. A review of the literature is presented.